Target Q-Coverage Problem with Bounded Service Delay in Directional Sensor Networks - Deying Li; Hui Liu; Xianling Lu; Wenping Chen; Hongwei Du (International Journal of Distributed Sensor Networks)
Maximizing network lifetime is an important objective for the target-coverage problem. With practicable manufacture and cost reduction, directional sensor has been widely used in wireless sensor networks to save energy. In this paper, we address the target Q-coverage (TQC) problem to prolong the network lifetime with bounded service delay constraint in directional sensor networks. We propose a protocol to find a collection of coverage sets that satisfy the coverage quality requirement and the bounded service delay constraint, where the target in each coverage set may not be served continuously but can be served with tolerant service delay. By steering some sensors' directional antennas, our protocol could deal with the changes of network topology or monitoring tasks. Simulation results show that the performance of our protocol is close to the upper bound of the optimal solution.